2018
DOI: 10.3390/ijms19020533
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat-Diet-Induced Obesity Produces Spontaneous Ventricular Arrhythmias and Increases the Activity of Ryanodine Receptors in Mice

Abstract: Ventricular arrhythmias are a common cause of sudden cardiac death, and their occurrence is higher in obese subjects. Abnormal gating of ryanodine receptors (RyR2), the calcium release channels of the sarcoplasmic reticulum, can produce ventricular arrhythmias. Since obesity promotes oxidative stress and RyR2 are redox-sensitive channels, we investigated whether the RyR2 activity was altered in obese mice. Mice fed a high fat diet (HFD) became obese after eight weeks and exhibited a significant increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…As expected, HFD increased plasma cholesterol levels in HFD compared with chow diet (Figure 1d). However, plasma triglycerides were similar in mice on HFD compared to chow diet (Figure 1d), in line with the previous report (Sanchez et al, 2018).…”
Section: Hfd Affects Body Weight and Plasma Lipidssupporting
confidence: 92%
“…As expected, HFD increased plasma cholesterol levels in HFD compared with chow diet (Figure 1d). However, plasma triglycerides were similar in mice on HFD compared to chow diet (Figure 1d), in line with the previous report (Sanchez et al, 2018).…”
Section: Hfd Affects Body Weight and Plasma Lipidssupporting
confidence: 92%
“…This promoted ventricular ectopy, which was significantly reduced in vivo by a mitochondrial-targeted antioxidant mitoTEMPO. Sánchez et al (2018) reported increased incidences of PVCs and non-sustained VT in HFD-mice vs. controls and this phenomenon was attributed to significantly increased RyR2 oxidation. When antioxidant apocynin was provided in the drinking water, appearance of ventricular arrhythmias in this model was completely abolished.…”
Section: Mechanisms Of Ca 2+ Dependent Arrhythmia mentioning
confidence: 96%
“…A significant increase in mitochondrial oxidative stress was suggested to increase RyR2 oxidation and subsequent SR Ca 2+ release. In 8-week mice with HFD-induced obesity, Sánchez et al (2018) reported a shift in the distribution of single RyR2 channel responsiveness to activating cytosolic [Ca 2+ ], whereby channels were much more active to those isolated from control mice. No changes were observed in RyR2 expression levels or phosphorylation status at S2808 or S2814 sites.…”
Section: The Ryanodine Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…Further, WT hearts had significantly more inducible ventricular tachycardia than NOX2 KO hearts after HFD. Part of the arrhythmic effect of NOX2 is due to activation of CaMKII, which phosphorylates the RyR2 channels [ 108 , 109 ]. This causes increased calcium leakage from the SR, which worsens mitochondrial function and promotes arrhythmias [ 27 , 77 ].…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%